Relationship between the Mediterranean Diet and Vascular Function in Subjects with and without Increased Insulin Resistance - Gómez-Sánchez, Marta; Gómez-Sánchez, Leticia; Llamas-Ramos, Rocío; Rodríguez-Sánchez, Emiliano; García-Ortiz, Luis; Martí-Lluch, Ruth; Rodríguez, María Cortés; Llamas-Ramos, Inés; Gómez-Marcos, Manuel A. (Nutrients, 2024)
(1) The main aim of this study was to analyze the relationship of the Mediterranean diet (MD) with vascular function in participants with and without increased insulin resistance (IR) in the Spanish population. A secondary aim was to study differences by gender. (2) Methods: Data were analyzed from 3401 subjects in the EVA, MARK, and EVIDENT studies (mean age = 60 years and 57% men). IR was evaluated with the triglyceride and glucose index (TyG index). TyG index = Ln [(fasting triglyceride mg/dL × fasting glucose mg/dL)/2]. The MD was measured against the MEDAS questionnaire, with the 14 items used in the PREDIMED study. Vascular stiffness was estimated with the brachial–ankle pulse wave velocity (baPWV) and the cardio ankle vascular index (CAVI) using the Vasera VS-1500®. (3) Results: The mean MEDAS value was 5.82 ± 2.03; (men: 5.66 ± 2.06; women: 6.04 ± 1.99; p < 0.001). MD adherence was 36.8% (men: 34.2%; women: 40.3%; p < 0.001). The mean baPWV value was 14.39 ± 2.78; (men: 14.50 ± 2.65; women: 14.25 ± 2.93; p = 0.005). A baPWV value ≥ 14.5 m/s was found in 43.4% (men: 43.6%; women: 40.0%; p = 0.727). The mean CAVI value was 8.59 ± 1.28; (men: 8.75 ± 1.28; women: 8.37 ± 1.26; p < 0.001). CAVI values ≥ 9 were present in 39.0% (men: 44.4%; women: 31.7%; p < 0.001). The mean value of the TGC/G index was 10.93 ± 1.39; (men: 11.08 ± 1.33; women: 10.73 ± 1.43; p < 0.001). IR was found in 49.9%. The average value of the MD score value was negatively associated with baPWV and CAVI in all groups analyzed (<0.05), except in the group of women with insulin resistance. (4) Conclusions: The results suggest that MD adherence is negatively associated with the vascular stiffness parameters analyzed in all the groups studied except the group of women with insulin resistance.